An Online Acquaintance Community: The Emergence of Chinese Virtual Civility. Issue 4 (19th January 2021) - Tian, Xiaoli; Guo, Yanan
Abstract : How is social etiquette performed when offline interpersonal interactions are mediated online? Sixty semi‐structured interviews with WeChat users, China's most popular social media platform, show that the app's technical designs facilitated a set of online etiquette rules which reproduced those of acquaintance communities. Three dimensions of social etiquette rules were considered and observed: respect, elegance, and tidiness. Users honored the face of others and avoided causing others to lose face, often presented a positive but restrained self‐image, and strived to preserve the tidiness of the online public space by avoiding the sharing of and exposing others to "negative energy." A video abstract is available at https://youtu.be/2tG40y8J11E .